Gestão estratégica da segurança do trabalho na área industrial de uma usina de etanol, açúcar e energia elétrica - Vicente, Fernando Antônio da Costa Figueiredo (2012)
Achieve profitability in a plant ethanol producer, sugar and electric power, without accidents at work, went on to be major challenge. Therefore, the Security Management has become strategic, seeking to bring business value "security" as a fundamental instrument in the implementation of production. Raise the history of implementation of the safety management System of the power plant and also we checked through universal indicators of security, if the numbers achieved satisfactory evolution, present trying to identify the actions taken and the results. In the process of evolution of that system, the plant became the first in the world in obtaining International certification (OHSAS 18001) security sector, as well as achieve Cosan 4th cane processing in Brazil. Applying the ICOS Instrument - Organizational Climate inventory safety in 2005 and again in 2011, we evaluate whether with production growth, coupled with the increase in the number of employees, the security value remained present. Apuramos also possible factors such as company time, schooling, proportion of accidents and interviews with officials who contributed to the existence of sectors there are 16 years without losing a day of work by accident. Finally, we found that deal with security management, empowers the company to face difficulties on the market, because success can not be worth today, for the following day in the event of an accident. Prevent, educate, seeking knowledge, celebrate, collect results, and daring, define plant's administration style studied.